Equipping parents to support their children's higher education aspirations: a design and evaluation tool. Issue 2 (4th March 2019) - Fischer, Sarah; Barnes, Robin Katersky; Kilpatrick, Sue
Abstract: This paper reviews the literature on best practices to engage parents in order to equip them to support their children's higher education aspirations. Parents from low socio-economic status (SES) backgrounds, in common with other parents, report that they want "the best" for their children's future. Getting a good education is a part of the aspiration of most parents, regardless of SES. However, unlike parents from mid and high SES backgrounds who usually have "educational cultural capital" to support their children's educational aspiration, parents from low SES backgrounds often are unable to confidently access information they need about possible education pathways within and beyond school. Additionally, they need to know where to find out about financial and other support resources available to facilitate access to higher education. Higher education participation by students from non-traditional backgrounds could be improved by outreach that promotes parents' social capital and "educational cultural" capital. This project has built upon University of Tasmania and University of Wollongong's combined experience, international literature and workshops with parent engagement practitioners to identify features of parent engagement programmes and resources that are efficient and effective in engaging parents from low SES backgrounds to support their children's higher education aspirations. From this, the higher education Design and Evaluation Matrix for Outreach was modified to develop a tool to plan, design, modify and evaluate parent engagement programmes.